PENYULUHAN PEMANFAATAN LAHAN PEKARANGAN DENGAN TANAMAN SAYURAN PADA KELOMPOK TANI BERSAMA DI DESA PADANG LUAS KECAMATAN KURAU KABUPATEN TANAH LAUT - Ahmad Baparki; Rohansyah; Norfajriah (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Utilizing yard land will provide benefits for family life, such as: a source of food and also as a source of income. A yard is an open area around a residence. Utilizing yard land will provide benefits for family life such as a source of food. A large yard will provide more space for planting. If you have a large yard, methods you can use include planting directly in the ground (beds), which can be combined using pots, polybags and verticulture. However, in a narrow yard, what can be done is to plant using planting media such as pots, polybags and verticulture and agricultural technology that can be applied to utilize yard land with hydroponic technology. The use of home gardens in the Joint Farming Group in Padang Luas Village, Kurau District, Tanah Laut Regency is one of the places that can be used by the community for various activities. One of the activities that can be done to utilize empty yard space is to use it for farming. Farming can not only be done in rice fields but can also be done in the yard of the house. So that it can increase community awareness regarding the use of home gardens which is still low. This can be seen by the large number of house yards that are not used and are left alone. So by utilizing this yard land, it means that you will be able to channel all the creativity and pleasure or hobbies of all members of the Farmer Group together and their family members. The main element in utilizing the yard is plants, whether they are horticultural plants, medicines, herbs, spices and especially vegetable plants